ФІЛОСОФСЬКІ ПІДХОДИ ДО РОЗУМІННЯ КАТЕГОРІЙ «ЗДОРОВ’Я/ХВОРОБА» - Біланов О. С. (International Journal of Innovative Technologies in Social Science, 2020)
The philosophical fundamentals of categories «health/illness» are analyzed; the genesis of the health concept in philosophical discourse and the basic semantic tinctures of «health/illness» concepts have been researched; the approaches to the understanding of the health in human philosophical doctrines have been analyzed and summarized.